Detection of frozen pork freshness by fluorescence hyperspectral image - Zhuang, Qibin; Peng, Yankun; Yang, Deyong; Wang, Yali; Zhao, Renhong; Chao, Kuanglin; Guo, Qinghui (Journal of food engineering, 2022)
Real-time detection of frozen meat freshness without thawing is important. This study investigates inspection of frozen pork quality attributes without thawing using fluorescence hyperspectral imaging (HSI). Partial least squares regression (PLSR) models were developed based on fluorescence spectra for total volatile basic nitrogen (TVB-N), pH, L*, a*, and b*, and compared with PLSR models based on visible/near-infrared (Vis/NIR) HSI of the same samples. Competitive adaptive reweighted sampling was used to select key fluorescence wavelengths related to each indicator. The correlation coefficients of prediction (Rp) of the models established by fluorescence spectra, with optimal pre-treatment for TVB-N, pH, L*, a*, and b*, were 0.9447, 0.9037, 0.6602, 0.8686, and 0.8699, respectively. Except for L*, fluorescence HSI-based model performance was better than that of Vis-NIR HSI. Model performance was further improved using selected key wavelengths. Results demonstrated that fluorescence HSI could determine freshness indicators of frozen pork without thawing. •Fluorescence HSI was used for the first time to assess frozen pork freshness.•Relationships between fluorescence peaks and freshness indicators were recognized.•PLSR models were compared based on fluorescence HSI and Vis/NIR HSI.•Key wavelengths were selected for each freshness indicators of frozen pork.